KPMG's True Value methodology: A critique of economic reasoning on the value companies create and reduce for society. Issue 4 (7th November 2016) - Coulson, Andrea B.
Abstract : Purpose: The purpose of this paper is to constructively critique KPMG's "True Value methodology" which seeks to quantify in financial terms the value companies create or reduce for society. Design/methodology/approach: This paper is based on a review of documents produced by KPMG detailing its methodology and corporate reports in the public domain of the True Value methodology applied in practice. The critique is divided into two sections. The first section reviews KPMGs methodological view of a bounded economic reality and offers potential starting points and limitations for a conceptual framing of the "methodology". Practical insights on applying the methodology are offered in the second section. Findings: The True Value methodology helps its producers understand the potential risk to future earnings posed by current externalities being internalised. KPMG's socio-economic framing of future scenarios and financial valuation of environmental and social impacts is limited to a standardised commercial viewpoint. Potential opportunities exist for producers to involve stakeholders in the application of the methodology to form a more inclusive and pluralist conception of risk and values for social and environmental impacts. Practical implications: This paper offers timely insights for companies using and considering the use of the "True Value" methodology and stakeholders considering their engagement in the application process and/or use of its findings. Originality/value: The study is a constructive critique of this contemporary, financial practice of accounting for externalities developed by KMPG.